Analysis of Community Health Center’s Employee Performance in Terms of Organizational Citizenship Behavior and Employee Engagement - Faridatul Fitriyah; Roro Aditya Novi Wardhani; Yusita Titi Hapsari (University of Muhammadiyah Malang, 2025)
This study aims to examine the influence of OCB and engagement on the performance of non-ASN employees at health centers Ajung, Jember. A quantitative survey method was applied, involving 33 purposively selected respondents. Data were gathered using a structured questionnaire and analyzed through multiple linear regression, following validity, reliability, and classical assumption testing. The results show OCB has a positive and significant effect on employee performance (sig. = 0.001), Employee engagement also has a positive and significant effect (sig. = 0.046), Together, OCB and engagement simultaneously affect performance with a contribution of 89.2% (R² = 0.892, sig. = 0.000). These findings indicate that both OCB and engagement are crucial in supporting optimal performance in public health centers, particularly in limited resource settings. This research provides practical implications for improving HR strategies in health centers, such as recognizing voluntary behavior, fostering employee commitment, and developing a supportive work environment. The results also enrich the academic discussion on public service motivation and HR performance models in healthcare.